Reading Comprehension Questioning Pattern Used by the Author of Elementary Students’ Workbook - Nadirah Febrianti Fitrah; Bibit Suhatmady; Istanti Hermagustiana; Ventje Jany Kalukar (Cetta: Jurnal Ilmu Pendidikan, 2026)
Reading comprehension is a fundamental skill that significantly influences students academic success across all subjects, particularly in elementary school. The questioning patterns employed in elementary students' workbooks significantly influence reading comprehension skills by guiding learners through varying levels of cognitive engagement. This qualitative study aimed to analyze the types and patterns of questions in elementary workbooks and explore their alignment with students' cognitive development stages. Employing a case study approach, the research involved document analysis of 100 questions from workbooks for grades 3, 4, and 5, categorized into factual, inferential, and open ended types, alongside semi-structured interviews with three students (one per grade) to capture preferences and experiences. The results revealed a predominance of factual questions (50%), followed by inferential (30%) and open ended (20%), with grade-specific distributions: Grade 3 (65% factual, 25% inferential, 10% open ended), Grade 4 (50% factual, 35% inferential, 15% open ended), and Grade 5 (35% factual, 35% inferential, 30% open ended). Student preferences aligned with cognitive stages, with younger students favoring factual questions and older ones preferring inferential and open ended types. In conclusion, while workbooks provide foundational comprehension practice, the imbalance toward factual questions may limit higher order thinking development. The study contributes to improving the design of reading materials aligned with students’ cognitive development, recommending a more balanced distribution of question types to foster progressive cognitive growth in elementary education.